1998
DOI: 10.1200/jco.1998.16.6.2052
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant lymphoproliferative disorders not associated with Epstein-Barr virus: a distinct entity?

Abstract: EBV-negative PTLD may be a late serious complication of organ transplantation. Half the tumors observed after kidney transplantation in our center were not associated with EBV and emerged after more than 5 years, which suggests the number of EBV-negative PTLDs in organ recipients might increase with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
226
7
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(252 citation statements)
references
References 34 publications
15
226
7
4
Order By: Relevance
“…In heart recipients, mortality from lymphoma was even higher -50% in the first year -and no improvement in survival was noted between patients transplanted recently or earlier ( Figure 8B). Contrary to claims in the literature (22,23,28,29) the time to development of lymphoma did not prognosticate survival in kidney or heart recipients. Five-year survival was 41.4% (n = 125) and 37.0% (n = 575) for kidney recipients whose tumors developed in <90 days or >365 days, respectively (p = NS); the corresponding 5-year survival rates in heart recipients were 33.3% (n = 42) and 30.0% (n = 398) (p = NS).…”
Section: Patient Survivalcontrasting
confidence: 99%
See 1 more Smart Citation
“…In heart recipients, mortality from lymphoma was even higher -50% in the first year -and no improvement in survival was noted between patients transplanted recently or earlier ( Figure 8B). Contrary to claims in the literature (22,23,28,29) the time to development of lymphoma did not prognosticate survival in kidney or heart recipients. Five-year survival was 41.4% (n = 125) and 37.0% (n = 575) for kidney recipients whose tumors developed in <90 days or >365 days, respectively (p = NS); the corresponding 5-year survival rates in heart recipients were 33.3% (n = 42) and 30.0% (n = 398) (p = NS).…”
Section: Patient Survivalcontrasting
confidence: 99%
“…Several reports have suggested differences between the clinical and biological characteristics of lymphomas that develop early or late after transplantation. Late-appearing lymphomas frequently lack EBV genome sequences, were reported to respond poorly to reduction or discontinuation of immunosuppression, and generally are believed to have a poorer outcome (22,23,28,29). In contrast to these reports, our data suggest that lymphomas have a poor outcome regardless of time of appearance after transplantation.…”
Section: Lymphomas After Solid Organ Transplantationcontrasting
confidence: 86%
“…The occasional EBV-negative PTLD occurs later (usually Ͼ2 years) after transplant and does not respond as well to withdrawal of immunosuppression. 24,25 PTLD-like tumors occasionally occur in patients who have not undergone transplant but who are immunosuppressed for other reasons, such as rheumatoid arthritis patients on methotrexate therapy. 26 As with PTLD, these tumors are often EBER-positive and respond favorably to immune reconstitution.…”
Section: Eber In Situ Hybridizationmentioning
confidence: 99%
“…Unlike post-transplant LPD, where $90% of the lesions contain evidence of EBV [1] about two-thirds of LPD in patients with rheumatologic disease are EBVnegative [14]. One author suggested that those cases of post-transplant LPD not associated with EBVare a distinct entity with poor outcome [15] The clinical picture of the presenting symptoms of LPD in children receiving chemotherapy for malignancy is quite variable, depending on the site of involvement (Table I). However, acute illness and extranodal organ involvement have been shared features in both the reported patients and the girl presented here.…”
Section: Discussionmentioning
confidence: 99%
“…There was no family record of familial malignancy or immunodeficiency. The girl was treated according to the ALL-BFM-95 standard risk protocol and remission was achieved on day 15. Week four of chemotherapy was complicated by severe pancreatitis, which was thought to be due to L-asparaginase.…”
Section: Introductionmentioning
confidence: 99%